1266 Intrauterine Growth Restriction and Very Preterm Birth are Associated with Motor Dysfunction and White Matter Pathology at School Age. (October 2012) - Morsing, E; Kahn, A; Ley, D; Björkman-Burtscher, I; Marsal, K
Abstract : Objective: To assess neuromotor ability and white matter (WM) pathology at early school age in children delivered at very early gestation due to intrauterine growth restriction (IUGR) with abnormal fetal blood flow. Design: Morphological 3T MRI and Movement assessment battery for children (ABC) were performed at median 8.5 years of age (range 7–11) in 27 children with IUGR and abnormal fetal blood flow born at a median of 26.9 (range 24–29) gestational weeks (PT-IUGR) to assess WM morphology and motor skills. Control groups were matched for gender and age and had birthweight appropriate for gestational age (AGA); 26 preterm (PT-AGA), born at 26.9 (range 24–29) gestational weeks and 28 term children (T-AGA). Results: Children with cerebral palsy in the PT-IUGR (n=3) and PT-AGA group (n=4) were excluded from further analysis. The PT-IUGR group had significantly higher rate of WM pathology compared to the T-AGA group (p<0.001) whereas PT-AGA did not differ from the other groups. WM pathology was found in 39%, 14% and 0% in the PT-IUGR, PT-AGA and T-AGA groups respectively. Higher scores on ABC, reflecting impaired motor skills, were found in the PT-IUGR mean (SD) 9.7 (5.5) compared to the PT-AGA 5.3 (4.1) and T-AGA 3.9 (3.7) children (p=0.004 and < 0.001, respectively). WM pathology found on MRI was not related to ABC-movement scores. Conclusion: IUGR with abnormal fetal blood flow in infants born very preterm has an additional negative impact on motor outcome and WM morphology at early school age.